PENINGKATAN PEMAHAMAN KONSTRUKSI BAGI PANITIA PEMBANGUNAN MASJID AT-TAQWA PERUMAHAN GRAND PURI BUNGA NIRWANA - Satoto, Eko Budi (Universitas Mataram, 2024)
The construction of mosques with comfort, safety and functional standards requires adequate human resources. Mosques in Indonesia are built independently by the community both coordinating financial resources and structural development. Therefore, the committee formed is not from the community but from human resources who have adequate abilities. The purpose of this activity is to increase the understanding and ability of construction implementation for the At-Taqwa mosque construction committee of Grand Puri Bunga Nirwana Housing in the perspective of comfort, safety and function. This community service activity begins with observation and coordination, the next steps in sequence are the preparation of materials and tools, guidance and counseling on mosque construction technology, Simulation of the Application of Mosque Construction Technology, Evaluation of the success of the PKM program is carried out by giving a pretest-posttest. After all the activities are running, a re-assessment is carried out. The average score obtained is 85. This value also shows that the error rate is below 20 percent. Therefore, it can be concluded that after being given training it has been successful or has been able to apply the technology for the construction of the At-Taubah mosque. The implementation of this community service activity has successfully completed all the steps of the service. The evaluation results showed that all participants who took part in the training had improved their abilities with an average score of 40.